Proposed Corporate Performance Management System For CV. Pelangi Nusantara - Assydik, Muhammad Handeriyan; Wibisono, Dermawan (Journal of Economics and Business UBS, 2024)
This research aims to design a performance management system suitable for the company. The design is created by translating the company's future objectives to enable growth and competitiveness. The research utilizes the Knowledge-Based Performance Management System (KBPMS) framework, as it can address the existing issues in the company. The KBPMS framework aims to assist companies that have not yet achieved their vision by utilizing all aspects owned by the company. There are three perspectives in KBPMS: organizational output, internal processes, and resource capabilities. This research results in a performance management system with 25 key performance indicators (KPIs) derived from the company's vision, mission, strategy, business processes, and discussions between the researcher and the company. It is hoped that by implementing the performance management system, the company can achieve its targets and develop its business lines to compete competitively.